Benign Metastasizing Leiomyoma: A Rare Type of Lung Metastases—Two Case Reports and Review of the Literature. (12th February 2014) - Taftaf, Rokana; Starnes, Sandra; Wang, Jiang; Shipley, Ralph; Namad, Tariq; Khaled, Rana; Abdel Karim, Nagla
Abstract : Benign metastasizing leiomyoma (BML) is a rare disease that usually occurs in women of reproductive age. They typically have history of uterine leiomyoma treated with hysterectomy. BML can metastasize to distant organs, with the lung being the most common organ. We report two patients who presented with benign metastasizing leiomyoma to the lung. Our first case was a fifty-two-year-old female who presented with multiple lung masses, with a past medical history of uterine leiomyoma who underwent hysterectomy 17 years ago. A CT-guided biopsy showed benign appearing spindle cells and pathology confirmed her diagnosis with additional positive estrogen/progesterone receptor stains. Our second case was a fifty-six-year-old female who presented with multiple cavitary pulmonary nodules. She subsequently underwent a video-assisted thoracoscopic surgery (VATS) with wedge resection of one of the nodules. Pathology confirmed the diagnosis based on morphology and immunohistochemical staining strongly positive for estrogen/progesterone receptors. Benign metastasizing leiomyoma is a rare condition which may affect women of reproductive age. This should be considered in the differential in patients who present with multiple pulmonary nodules, especially with a history of uterine leiomyoma. Additional stains, such as estrogen/progesterone receptors, may need to be done to confirm the diagnosis.